Response of coagulation factors to different high intensity interval exercise protocols in young overweight men - Masoumeh Hatamy; Hiva Rahmani (Shahid Beheshti University, 2021)
Purpose: The aim of this study was to investigate the response of coagulation factors to different high intensity interval exercise protocols in young overweight men.Methods: Ten young overweight (BMI of 26.5 ± 1.43) were selected as subjects. After determination of their peak power output, Subjects performed two protocols of high intensity interval exercise in two next sessions: 110% of PPO, 6 reps 30 seconds with 3.5-minute active recovery and 85% of PPO, 6 reps 2 minutes with 2 minutes active recovery, one week apart. Analyzes were performed before and immediately after each protocols. The independent t-test is used to compare means of two groups. Significance levels were set at P ≤ 0.05 for all statistical analyses. Results: The results showed that regardless of the protocol types, high intensity interval training session had no significant effect on of PT (P > 0.05), but the differences of PT responses in two protocols was significant (P < 0.05). A High-intensity interval training session had no significant effect on PTT and fibrinogen (P > 0.05). Evaluation the responses of these variables to protocols values showed no significant differences (P > 0.05).Conclusion: Although the intensity of the activity relatively increased coagulation factors and decreased clotting time but interval exercise protocol was not had minimal differences on coagulation factors. Probably, Because of small changes in fibrinogen as one of acute phase proteins with these HIIT protocols, they could be useful training method for inactive people